2015
DOI: 10.1021/ed5009415
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Quantum Dots: A Case Study Using PbS

Abstract: A research project for senior undergraduates of chemistry has been developed to introduce syntheses of a series of monodispersed semiconductor PbS quantum dots (QDs) and their characterization methodologies. In this paper, we report the preparation of monodispersed semiconductor PbS QDs with sizes smaller than the exciton Bohr radius using a simple, one-step process, and the characterization of the QDs using a range of instruments, including Fourier-transform infrared spectroscopy, transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Chemical functionalization of the QD surface is a powerful and versatile strategy to tune the energies and spatial distributions of core and surface states of colloidal QDs because the surface ligands control (i) the degree of surface enrichment of cations or anions, (ii) the degree of coordination of surface ions (how electron rich or electron poor they are), (iii) in some cases, the magnitude of the confinement energy of excitonic charge carriers, and (iv) the crystal structure and the size of QDs, when those ligands are present as surfactant in the reaction mixture. Common protocols to prepare colloidal QDs ,, produce QDs terminated with aliphatic organic molecules, such as alkyl carboxylates, alkyl phosphonates, or alkylamines. With dependence on the particular application of the QDs, these ligands can be replaced after synthesis with a large variety of organic molecules, ,, in order to tune the electronic structure of the nanoscale interface and, in some cases, the electronic structure of the QD’s core.…”
Section: Role Of Molecules In the Electronic Structure Of Colloidal Qdsmentioning
confidence: 99%
“…Chemical functionalization of the QD surface is a powerful and versatile strategy to tune the energies and spatial distributions of core and surface states of colloidal QDs because the surface ligands control (i) the degree of surface enrichment of cations or anions, (ii) the degree of coordination of surface ions (how electron rich or electron poor they are), (iii) in some cases, the magnitude of the confinement energy of excitonic charge carriers, and (iv) the crystal structure and the size of QDs, when those ligands are present as surfactant in the reaction mixture. Common protocols to prepare colloidal QDs ,, produce QDs terminated with aliphatic organic molecules, such as alkyl carboxylates, alkyl phosphonates, or alkylamines. With dependence on the particular application of the QDs, these ligands can be replaced after synthesis with a large variety of organic molecules, ,, in order to tune the electronic structure of the nanoscale interface and, in some cases, the electronic structure of the QD’s core.…”
Section: Role Of Molecules In the Electronic Structure Of Colloidal Qdsmentioning
confidence: 99%
“…reported that the size of PbS QDs can be varied from 2 to 16 nm, resulting in bandgaps of 1.8 to 0.5 eV. [ 29 ] Following the development of methods to enhance the conductivity of QD films through short‐ligand exchange, PbS QDs have begun to be used for solar cell research in earnest. In the case of single active cells, PbS QDs with excitonic absorption peaks at wavelengths as long as 950 nm have been used to fabricate solar cells with the best performance since the first depleted heterojunction solar cell architecture was proposed.…”
Section: Optical Design For Qd Pvsmentioning
confidence: 99%
“…This fundamental nanochemistry concept has been frequently illustrated in this Journal . Laboratory experiments using QDs have made use of CdSe, CdS, , ZnO, , C, , PbS, , Cu 2 O, and CsPbX 3 . QDs are an intriguing material for applications in solar cells, , in video displays, as hydrolysis photocatalysts, in white LED lighting, in photoluminescent labeling for bioimaging, and for cancer treatment .…”
Section: Introductionmentioning
confidence: 99%